Penerapan Sanksi Administratif Kepada Masyarakat Berdasarkan Peraturan Gubernur - Herman Yudiawan, I Dewa Gede; Trisna Adi Putra, I Komang (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2021)
The Covid-19 pandemic situation that has occurred this year has forced the government to issue all policies to regulate the public to avoid or reduce the risk of contracting the Covid-19 virus. The Bali Governor Regulation 46 of 2020 aims as stipulated in Article 3, namely to prevent and control the spread of the Covid-19 virus in various sectors in the Province of Bali. It is also seen in Law 23 of 2014 concerning Regional Government, in particular Article 238 paragraph (4) where administrative sanctions can only be regulated in Regional Regulations. Specifically, regarding administrative sanctions such as what was previously regulated in the Bali Governor Regulation No. 46 of 2020, it is a sanction given to people who violate health protocols which during the Covid-19 pandemic are getting serious handling from the authorities. The administrative sanctions in the Bali Governor Regulation No. 46 of 2020 are regulated in Article 11 paragraph (2). Based on the Presidential Instruction of the Republic of Indonesia Number 6 of 2020 concerning Improvement of Discipline and Law Enforcement of Health Protocols in the Prevention and Control of Corona Virus Disease 2019, Bali Governor Regulation No. 46 of 2020. The inclusion of administrative sanctions on the people in Bali is Rp. 100.000,- for people who are in the wild in the room/house not wearing a mask, it is an instruction previously issued by the President which instructs regional heads to impose sanctions, one of which is administrative fines for the community, and for the amount of the sanctions which are determined by the Governor.